Bortezomib protects from varicose-like venous remodeling - Pfisterer, Larissa; Meyer, Ralph; Feldner, Anja; Drews, Oliver; Hecker, Markus; Korff, Thomas (The FASEB journal, 2014)
Despite the high prevalence of venous diseases that are associated with and based on the structural reorganization of the venous vessel wall, not much is known about their mechanistic causes. In this context, we demonstrated that the quantity of myocardin, a transcriptional regulator of the contractile and quiescent smooth muscle cell phenotype, was diminished in proliferating synthetic venous smooth muscle cells (VSMCs) of human and mouse varicose veins by 51 and 60%, respectively. On the basis of the relevance of proteasomal activity for such phenotypic changes, we hypothesized that the observed VSMC activation is attenuated by the proteasome inhibitor bortezomib. This drug fully abolished VSMC proliferation and loss of myocardin in perfused mouse veins and blocked VSMC invasion in collagen gels by almost 80%. In line with this, topical transdermal treatment with bortezomib diminished VSMC proliferation by 80%, rescued 90% of VSMC myocardin abundance, and inhibited varicose-like venous remodeling by 67 to 72% in a mouse model. Collectively, our data indicate that the proteasome plays a pivotal role in VSMC phenotype changes during venous remodeling processes. Its inhibition protects from varicose-like vein remodeling in mice and may thus serve as a putative therapeutic strategy to treat human varicose veins.—Pfisterer, L., Meyer, R., Feldner, A., Drews, O., Hecker, M., Korff, T. Bortezomib protects from varicose-like venous remodeling. FASEB J. 28, 3518-3527 (2014). www.fasebj.org